HEARING IMPROVEMENT IN PATIENTS WITH COMMUNICATIVE DISORDERS - Alexander Donchev; Mario Milkov (Peytchinski Publishing, 2019)
For intervention of any communication disorder, prevention is the first and crucial component. A communication disorder is an umbrella term, which includes a variety of speech, language, and hearing disorders. Hearing impairment and hearing loss cause considerable damage to communication skills in children and adults. The communication disorders require timely and proper interventions by interdisciplinary teams. In the present survey, some effective clinical practices reported in the current world literature are concisely described.